EXPANDING THE USE CASE GRAIN PROCESSING PRODUCTS IN BAKERY PRODUCTS - S. A. Romanchikov; I. P. Yukhnik (Современная наука и инновации)
One of the most pressing problems is the use of various types of modified starches in baked bakery products. Such starches can be obtained from low-quality grain, which usually accounts for a significant part of the losses during storage. The processing of such grain into useful ingredients for use in the production offood is ofparticular relevance in the absence of specialized starch-treacle production facilities near the storage facilities, for example, in the Far North, shift settlements and other areas with a compact population deprived of the possibility of regular replenishment of food.